Do observers have a better memory for a negative emotional event than actors? : the relationships between involvement level, information and memory task. - Chin, Yammie Shi Yun. (2009)
The present study seeks to investigate whether the passive role (e.g. observer) typically played by laboratory eyewitnesses leads to an overestimation of memory for a negatively emotional event as compared to real-life eyewitnesses who are usually also actors in the event. Results showed that observers (n = 39) remembered more details about the event, without a significant increase in errors, than actors who made response choices from similar alternatives (n = 34), but not those who selected from dissimilar alternatives (n = 37). Control beliefs are not predictive of memory. While memory for central information is better than peripheral information in the free recall task, it is worse in the recognition task. The implications of these findings are discussed.